Living Qur’an Dalam Karya Seni Lukis - Faruq, Umar; Hamzah, Amir (Institut Seni Indonesia Yogyakarta, 2022)
The creation of this paintings explains the effort to bring back the meaning summarized in one concept of the Living Qur'an into the form of a painting. The effort made is to perceive, interpret and explore the form of the Qur'an according to personal interpretation by involving the imagination of its cultural awareness in the process of creating a painting. After receiving, the ideas that are born are transformed into visual forms of painting by using abstractions that are closely related to the noble values of the Qur'an. While the problems that are responded to in the work talk about the noble value of the existence of the verses of the Qur'an that live in society, both from ancestors to today's society. In this context, the creation that is conveyed cannot be separated from the historical, myth, belief, cultural and social context in the area where the author was born, namely the village of Bagelen Bagelen, Purworejo. The concept of creating this final project is divided into three types, namely the writer's reception of the Qur'an, the reception of the letters of the Qur'an, and the reception of the Qur'anic culture. This creation is an attempt to reflect on these historical phenomena, such as the tradition of tahlilan, mapati, akikah, to the rajahs that have been passed down from generation to generation from their parents. Penciptaan karya seni lukis ini menjelaskan upaya menghadirkan kembali makna yang terangkum dalam satu konsep Living Qur’an ke dalam wujud karya seni lukis. Usaha yang dilakukan adalah dengan meresepsi, memaknai dan mengeksplorasi bentuknya Al Qur’an menurut interpretasi pribadi dengan melibatkan imajinasi dari kesadaran kulturalnya dalam proses penciptaan karya seni lukis. Setelah meresepsi, ide-ide yang lahir ditransformasikan kedalam bentuk visul karya seni lukis dengan menggunkan abstraksi-abstraksi yang lekat dengan nilai- nilai luhur Qur’ani. Sementara permasalahan yang direspon dalam karya berbicara tentang nilai luhur eksistensi ayat-ayat Al-Qur’an yang hidup dalam masyarakat baik dari leluhur hingga masyarakat saat ini. Dalam konteks ini, penciptaan yang disampaikan tidak lepas dari konteks sejarah, mitos, kepercayaan, kebudayaan dan sosial di daerah penulis dilahirkan, yaitu desa Bagelen Bagelen, Purworejo. Konsep penciptaan tugas akhir ini terbagi dalam tiga macam, yaitu resepsi penulis atas Al- Qur’an, resepsi atas huruf-huruf Al-Qur’an, dan resepsi atas kebudayaan Al-Qur’an. Penciptaan ini merupakan upaya dalam merefleksikan fenomena-fenomena bersejarah tersebut, seperti halnya tradisi tahlilan, mapati, akikah, hingga pada rajah-rajah yang turun temurun dari orang tuanya.